The problem of Jesus answering a skeptic's challenges to the scandal of Jesus - Clark, Mark A. 1980- (Grand Rapids Zondervan, 2021)
"In The Problem of Jesus, author and pastor Mark Clark looks beyond the superficial understandings of Jesus. He confronts you with the real Jesus of history, asking you to wrestle with the teachings, claims, and actions of the man who has forever altered the course of human history"--
Keywords: Jesus Christ; Apologetics